Juridical Review Of Standard Agreements In The Framework Of Consumer Protection - Diana Pujiningsih (Ipso Jure, 2024)
Exonerating clauses have been widely used in agreements due to their time and cost efficiency. However, as the use of these clauses has expanded, there have been instances of non-compliance with certain requirements, which have subsequently caused disadvantages to certain parties. Exonerating clauses are often employed in freight forwarding service agreements by companies to limit their legal liability in the event of loss or damage to a consumer's goods. From the perspective of consumer protection, the use of exonerating clauses can create an imbalance in rights and obligations between service providers and consumers. According to Law No. 8 of 1999 on Consumer Protection, consumers have the right to safety, comfort, and security in the consumption of goods and services. However, exonerating clauses can undermine or limit these rights, potentially causing harm to consumers. This paper will discuss the use of exonerating clauses in freight forwarding service agreements from the perspective of consumer protection based on the Consumer Protection Act. It will focus on how these clauses can be used unfairly by companies to avoid liability and how the law should protect consumers from such detrimental practices. This analysis is crucial to ensuring that the use of exonerating clauses does not conflict with the fundamental principles of consumer protection established by law.